Formulation of Granular Fertilizer from Elephant Grass Ash and Urea with Tapioca Binder - Yuriko Tiara; Meriska Diva Nadia Putri Amrulloh; Ketut Sumada (Universitas Islam Raden Rahmat, Malang, 2025)
Elephant grass remains underutilized, despite its ash containing high levels of potassium and its potential as a raw material for fertilizer production. This study aims to evaluate the effect of mixing ratios of elephant grass ash and urea with tapioca starch binder on fertilizer composition in accordance with quality standards, and to examine how binder concentration influences the characteristics of the resulting granules. The process began by burning elephant grass into charcoal, followed by ashing in a furnace at 600°C for 4 hours. The ash was then mixed with urea and tapioca starch at various compositions. The variables included urea additions of 20%, 25%, 30%, 35%, and 40% (w/w), and binder concentrations of 6%, 7%, 8%, 9%, and 10% (w/w). The resulting granules were analyzed for N, P₂O₅, and K₂O content to determine the optimal formulation. The study found that granules with 20% urea met the standard of Indonesian Ministry of Agriculture Regulation No. 209/Kpts/SR.320/3/2018, while granules with 10% tapioca binder had the longest disintegration time at 413 minutes. This research contributes to the development of sustainable fertilizers derived from elephant grass biomass waste.